2021
DOI: 10.1136/bmjoq-2021-001404
|View full text |Cite
|
Sign up to set email alerts
|

Increasing adherence to plotting e-partograph: a quality improvement project in a rural maternity hospital in India

Abstract: Abnormal prolonged labour and its effects are important contributors to maternal and perinatal mortality and morbidity worldwide. E-partograph is a modern tool for real-time computerised recording of labour data which improves maternal and neonatal outcome. The aim was to improve the rates of e-partograph plotting in all eligible women in the labour room from existing 30% to achieve 90% in 6 months through a quality improvement (QI) process.A team of nurses, obstetricians, postgraduates and a data entry operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…When we go to a root level and do a PDSA cycle, we don't need multiple studies to find barriers -one study is sufficient as ours. But how to find its solution is mentioned in limited studies [11][12][13], to the best of our literature review. According to Bedwell et al [25] in a realistic review, 'There is a limited description of implementation strategies in the reviewed literature' but our study found the solution to these problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When we go to a root level and do a PDSA cycle, we don't need multiple studies to find barriers -one study is sufficient as ours. But how to find its solution is mentioned in limited studies [11][12][13], to the best of our literature review. According to Bedwell et al [25] in a realistic review, 'There is a limited description of implementation strategies in the reviewed literature' but our study found the solution to these problems.…”
Section: Discussionmentioning
confidence: 99%
“…We have not used perforated margins as we don't have to refer patients. Another quality improvement study was done by Jain et al in 2022 [13] in a tertiary care centre for using e-partograph. They have also focused on the training, allocation of triage, and assigning responsibility to sisters for filling e-partograph.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-identification of high-risk pregnancies to improve triaging at the time of admission and management of complications in labour room: a quality improvement initiative 21 Increasing adherence to plotting e-partograph: a quality improvement project in a rural maternity hospital in India 17 Paediatrics Institution of an antibiotic stewardship programme for rationalizing antibiotic usage: a quality improvement project in the NICU of a public teaching hospital in rural central India 19 Zero neonatal hypothermia around birth…”
Section: Obstetrics and Gynaecologymentioning
confidence: 99%
“…Digitizing the partograph improves adherence and overcomes the limitation of paper-based partographs [10,16,[20][21][22]. The electronic partograph is a contemporary instrument for capturing labor data in real time, which can improve mother and infant outcomes [23]. Electronic partographs make it possible to improve the labor management system's record of labor progress statistics and care given to mother and fetus, especially in low-income nations [10,20,24,25].…”
Section: Introductionmentioning
confidence: 99%